2015
DOI: 10.3389/fonc.2015.00070
|View full text |Cite
|
Sign up to set email alerts
|

P62/Ubiquitin IHC Expression Correlated with Clinicopathologic Parameters and Outcome in Gastrointestinal Carcinomas

Abstract: P62 and ubiquitin are small regulatory proteins demonstrated to have implications in the prognosis and survival of various malignancies including: hepatocellular, breast, ovarian, and some gastrointestinal carcinomas. Several trials studied the link of their activity to the extrinsic apoptosis pathway and showed that their autophagy modification has a critical stand point in tumorigenesis. These findings explain their vital role in controlling the process of cell death and survival. It has been shown recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 16 publications
0
36
1
Order By: Relevance
“…Since p62 is an autophagy substrate, a high level of p62 in the cytoplasm may indicate suppressed or defective autophagy, resulting in altered NF‐kappa B‐related gene expression and promotion of tumorigenesis . Furthermore, p62 overexpression presumably related to an autophagy defect has been found in a number of human cancers . In a recent study, a stronger cytoplasmic expression of p62 was found in HCC compared with non‐neoplastic liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since p62 is an autophagy substrate, a high level of p62 in the cytoplasm may indicate suppressed or defective autophagy, resulting in altered NF‐kappa B‐related gene expression and promotion of tumorigenesis . Furthermore, p62 overexpression presumably related to an autophagy defect has been found in a number of human cancers . In a recent study, a stronger cytoplasmic expression of p62 was found in HCC compared with non‐neoplastic liver.…”
Section: Discussionmentioning
confidence: 99%
“…MDBs only 17 ( related to an autophagy defect has been found in a number of human cancers. [28][29][30][31][32][33][34] In a recent study, a stronger cytoplasmic expression of p62 was found in HCC compared with non-neoplastic liver. Therefore, p62 has been proposed as a novel tumour marker for HCC.…”
Section: Sh-hcc a N (%)mentioning
confidence: 99%
“…P62 is a scaffold protein involved in a variety of cellular processes including NF-kB-signaling [ 31 , 50 , 51 ]. Recently, a correlation of p62 expression with clinicopathologic parameters has been shown for prostate cancer and gastrointestinal carcinoma [ 52 , 53 ]. Under obatoclax treatment we observe an accumulation of p62, which is indicative for a late stage autophagy inhibition, since the scaffold protein is trapped in the autophagic vesicle.…”
Section: Discussionmentioning
confidence: 99%
“…p62 is ubiquitously expressed in various cell types , mainly in the cytoplasm, and is also present in the nucleus, autophagosomes, and lysosomes . p62 is overexpressed in many types of human cancer, including hepatocellular carcinoma (HCC) , intrahepatic cholangiocarcinoma , pancreatic cancer , lung cancer , oral, head and neck cancer , esophageal cancer , gastric cancer , colon cancer , breast cancer , prostate cancer , melanoma , endometrial cancer , ovarian cancer , and kidney cancer , as well as chronic liver diseases, such as alcoholic and nonalcoholic steatohepatitis (ASH, NASH) that increase HCC risk . Therefore, a p62‐encoding DNA plasmid vaccine may be useful for cancer immunotherapy .…”
Section: Regulation Of P62 Expressionmentioning
confidence: 99%